Erratum to ‘Should post-operative stereotactic radiosurgery be the standard of care in Craniopharyngioma patients?’ [World Neurosurgery: X (22C) (2024) 100327] - Saurabh Gupta; Deepak Agrawal; Shweta Kedia; Shashank Sharad Kale (World Neurosurgery: X)
Objective: This study aims to analyse clinical and radiological outcomes in patients receiving adjuvant gamma knife radiosurgery (GKRS) for residual craniopharyngiomas. It compares these outcomes with patients who did not receive post-operative GKRS. Methods: In this retro-prospective case–control study, we enrolled all consecutive patients who received adjuvant GKRS for recurrent/residual craniopharyngiomas from.2011 to 2019, with a minimum 12 month radiological follow-up. Consecutive surgically treated craniopharyngioma patients between 2018 and 2019, who did not receive any post-operative radiotherapy constituted the control group. The clinical, and radiological outcomes were compared between the two groups. Results: A total of 79 patients were analyzed. 35 patients received GKRS in the post-operative period, with a median age of 21 years (range 6–55 years). At a median follow-up of 60.1 months (range 24–118 months), the tumor control rate was 91.4 % (n = 32). In the control group there were a total of 44 patients, with a median age of 16 years (range 3–48 years), and a median follow-up of 47.4 months (range 12.7–61.7 months). Kaplan–Meier analysis, and log-rank tests showed better 3-year PFS (92.3 % vs. 77.7 %, p = 0.03), and 3-year OS (97.1 % vs. 74.6 %, p = 0.009) for patients who received post-operative GKRS. Cox proportional-hazards showed post-operative GKRS (HR = 0.055, 95 % CI = 0.008–0.363) to be an independent prognostic factor for OS in craniopharyngioma patients. Conclusion: This study shows that GKRS offers improved clinical and radiological outcomes as compared to surgery alone, and should be considered in all patients with residual disease.